A new scenario resource for integrated 1.5 °C research. Issue 12 (December 2018) - Huppmann, Daniel; Rogelj, Joeri; Kriegler, Elmar; Krey, Volker; Riahi, Keywan
Scenarios have supported assessments of the IPCC for decades. A new scenario ensemble and a suite of visualization and analysis tools is now made available alongside the IPCC 1.5 °C Special Report to improve transparency and re-use of scenario data across research communities.